Technology, Urban Space and the Networked Community - Das, Saswat Samay; Pratihar, Ananya Roy. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This collection stages a dynamic scholarly debate about the ambivalent workings of technocapitalism and humanism in urban spaces. Such workings are intended to provide multiple forms of autonomy and empowerment but instead create intolerable contradictions that are experienced in the form of a slavish adherence to machines. Representing the novelty of a post-anthropocentric grammar, this book points towards a new ethical and political praxis. It challenges the anthropocentrism of bio-politics and neoliberalism in order to express the constitutive potential of an eco-sensible 'new earth'. Dr. Saswat S. Das is an Associate Professor in the Department of Humanities and Social Sciences, Indian Institute of Technology, Kharagpur, India. He is the co-author of Taking Place of Language (2013) and the co-editor of Deleuze, Guattari and the Global Pandemics (forthcoming). His book reviews are regularly published in Postcolonial Studies, South Central Review, Cultural Politics, French Studies, and Philosophy in Review. Dr. Ananya Roy Pratihar is Assistant Professor in Communication Studies at the Institute of Management and Information Science, Bhubaneswar, India. She is the co-editor of Deleuze, Guattari and the Global Pandemics (forthcoming). Her book reviews and articles are published in Philosophy in Review and Exchanges.
Chapter 1.Biopolitics, Discipline and Governmentality.-Chapter 2.The Market Lives on Death: The Endocolonizing Logic of the Fascist Moment.-Chapter 3.Technology and Biopolitics: A Deleuzian Perspective.-Chapter 4.The Quandaries of Machinic Subjectivity in Félix Guattari's Chaosmosis.-Chapter 5.Fabulation in a Time of Algorithmic Ecology: Making the Future Possible Again.-Chapter 6.The Surveillance Axiomatic -- Chapter 7.Inside the Matrix: Matriarchs, Materialisms, and Machinic Being.-Chapter 8.Posthuman Urban Spaces in Dave Eggers' The Circle -- Chapter 9.From Miasma Theory to Digital Ghost Town: Tales of Infrastructure and Social Politics in the 21st Century Megalopolis.-Chapter 10.THE IN/VISIBLE CITY: Cinema, Control and Contemporary Hong Kong.-Chapter 11.Techno-Medieval: Rise and Fall of Contemporary Metropolitan Networks.
Keywords: Technology-Philosophy.; Philosophy and social sciences; Philosophy of Technology; Philosophy of the Social Sciences